Novel Preparation and Physicochemical Characterization of a Nanocrystalline Cobalt Ferrite System - N.M. Deraz; M.K. El-Aiashy; Suzan A. Ali (Adsorption Science & Technology, 2009)
Well-defined CoFe 2 O 4 nanoparticles with an average grain size of about 50 nm were successfully synthesized by a combustion method employing different ratios of fuel to cations within the range 0–2.67. The as-prepared powders were characterized and investigated by TG, XRD, IR, SEM, TEM and VSM methods, and via isopropanol conversion at 250–450 °C. The results showed that increasing the ratio between fuel and cations stimulated the formation of cobalt ferrite due to the increasing flame temperature. Changing the fuel/cation ratio brought about modifications in the structure, surface activity, selectivity and magnetic properties of the investigated solids. A fuel/cation ratio of 2 led to the formation of catalyst having a high activity (49%) and magnetization (77.54 emu/g). All the solids investigated behaved as dehydrogenation catalysts leading to the formation of acetone as the major product. The fuel/cation ratio did not alter the mechanism of dehydrogenation of isopropanol, but increased the concentration of active sites involved in the catalyzed reaction.